216 Open Versus Minimally Invasive Surgery (MIS) Transforaminal Lumbar Interbody Fusion (TLIF): A Single-Centre Experience. (28th February 2022) - Eldoadoa, M.; Aldarragi, A.; Rao, P.; Sian, P.; Kapoor, V.; Mazarakis, N.K.
Abstract: Introduction: Transforaminal Lumbar Interbody Fusion (TLIF) is a technique used for the management of various pathologies such as degenerative disc disease, recurrent disc herniations and spondylolisthesis, to mention the most common indications. There is an ongoing debate regarding the use of open versus minimally invasive techniques for TLIF. Each has its own advantages and disadvantages. In the present study, we aim to present our experience regarding the use of open vs MIS TLIF at Stepping Hill Hospital in Manchester. Method: A retrospective observational cohort study involving 60 patients was conducted at Stepping Hill Hospital in the UK. Patients who had TLIF surgery between 2019 and 2020 were included. Patients were consecutively allocated to either the open TLIF or the MIS TLIF group. Data were collected from hospital records including pre- and post-operative follow up notes. We also assessed pain score using the visual analogue scale. Results: 26 patients underwent MIS TLIF whereas 34 patients underwent an open procedure. The MIS group showed better outcomes compared to the open group in terms of post-operative complications, improvement of symptoms and the average hospital stay: 7.6% vs 8.8%, 73.7% vs 58.8% and 1.82 vs 2.76 days, however, the open group had a lower rate of metalwork failure 8.8% vs 11.5% in the MIS. Conclusions: Our study showed that MIS TLIF at our unit seems to result in better outcomes related to symptoms alleviation, post-operative complications and less hospital stay despite having a slightly higher rate of metalwork failure.